PARTICULAR CHARACTERISTICS OF SIMULTANEOUS INTERPRETATION - Eshonqulov Azamat Sanjar o’g’li (Scholar Express Journal, 2022)
The current article is devoted to the particular theoretical views of simultaneous interpretation. Many scholars view interpreting as a form of translation. Based on that assumption, interpreting studies are expected to benefit from the theory and research in the field of translation. However, interpreting studies has benefited from translation studies only to a very limited degree. Therefore, particular characteristics of simultaneous interpretation require to be investigated in details prior to analyzing them in practical sense. Interpreting is commonly believed to be one of the most cognitively demanding language tasks. Simultaneous interpreting, also involves processes and skills such as: self-monitoring, memory skills, verbal fluency and concurrent listening and production. In order to provide a high-quality interpretation, the interpreter needs to master all of these above-mentioned skills. The question of interpreters’ aptitude has been widely discussed in the context of this article.
Keywords: Synchronic; aptitude; complexity; Commission